Delipid extracorporeal lipoprotein filter from plasma system: a new intensive lipid lowering therapy for patients with acute ischemic stroke - Jiao, Yuqiong; Yang, Qi; Ye, Ting; Zhu, Jun; Li, Qunyi; Han, Xiang; Dong, Qiang (Frontiers in Neurology, 2024)
Objectives To investigate the safety and efficacy of the delipid extracorporeal lipoprotein filter from plasma (DELP) system, a new low-density lipoprotein cholesterol (LDL-C) adsorption system, in acute ischemic stroke (AIS) patients. Patients and methods In the present study, a total of 180 AIS patients were enrolled during March 2019 to February 2021. They were divided into DELP group (n1 = 90) and the control group (n2 = 90). The treatment protocol and vascular access of DELP treatment was established and evaluated. For the DELP group, clinical data and laboratory results including plasma lipid and safety parameters before and after the apheresis were collected and analyzed. For all participants, neurological scores were assessed and recorded. Results For the DELP group, 90 patients including 70 males and 20 females were included. The mean LDL-C was significantly decreased from 3.15 ± 0.80 mmol/L to 2.18 ± 0.63 mmol/L (30.79%, p < 0.001) during a single DELP treatment, and decreased from 3.42 ± 0.87 mmol/L to 1.87 ± 0.48 mmol/L (45.32%, p < 0.001) after two DELP treatments. No clinically relevant changes were observed in hematologic safety parameters and blood pressure levels except for hematocrit and total protein throughout the whole period of DELP treatment. The DELP group showed improvement relative to the control group in National Institute of Health stroke scale scores (NIHSS) on the 14th and 90th day after stroke. Moreover, the DELP group had a significantly higher ratio of mRS 0 to 1 on the 90th day after stroke. Conclusion The new LDL-C adsorption system, the DELP system, may provide a new option for intensive lipid lowering therapy in AIS patients in view of its safety, efficacy, and operation feasibility.